Peluang Dan Tantangan UMKM Dalam Pemanfaatan QRIS - Gusman Gusman; Arianto Saputra Daeli; Hendi Gunawan; Jeksen Jeksen; Michael Fernando (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The development of digital technology, especially in the financial sector, has brought significant changes to the way transactions are carried out, especially in the Micro, Small and Medium Enterprises (MSME) sector in Indonesia. QRIS (Quick Response Code Indonesian Standard) is here as a solution to facilitate non-cash payments, which were previously limited for many MSME players. This research aims to explore the opportunities and challenges faced by MSMEs in implementing QRIS as a digital payment method. The research method used is a qualitative approach with literature study, utilizing data from journals and scientific articles related to financial technology and digitalization of MSMEs. The research results show that QRIS provides a great opportunity for MSMEs to increase financial inclusion, expand markets and increase operational efficiency. However, the challenges faced by MSMEs in adopting QRIS include a lack of technological understanding, limited internet infrastructure, high technology integration costs, and digital transaction security issues. This research also provides several suggestions for optimizing the use of QRIS, including through educational campaigns, collaboration with digital platforms, increasing transaction security, access to financing, as well as regular monitoring and evaluation. With these steps, QRIS is expected to accelerate digital transformation in the MSME sector and encourage more inclusive digital economic growth in Indonesia.